INDONESIAN FOR EARLY AGE: LEARNING THROUGH THE EARLIEST DISCOVERIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A boy at an early age are expected to gain proficiency in speaking and writing through the understanding of the inventors ; count early , tool first weaponry, rolling early , firemaking ancient times, chemists first.